2004
DOI: 10.1093/bioinformatics/bth391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pooling mRNA in microarray class comparisons

Abstract: Supplementary material referenced in the text is available at http://linus.nci.nih.gov/brb/TechReport.htm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 10 publications
1
60
0
Order By: Relevance
“…Appropriate pooling has been shown to improve efficiency for microarray experiments (Peng et al 2003). One study, however (Shih et al 2004), found discordances between the average expression of individual samples and that of a corresponding pool sample, the magnitude of the discordance in each probe set increasing monotonically with its signal in the microarray. In any case, this effect was not associated with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate pooling has been shown to improve efficiency for microarray experiments (Peng et al 2003). One study, however (Shih et al 2004), found discordances between the average expression of individual samples and that of a corresponding pool sample, the magnitude of the discordance in each probe set increasing monotonically with its signal in the microarray. In any case, this effect was not associated with our results.…”
Section: Discussionmentioning
confidence: 99%
“…probe sets was divided in 20 intervals according to their mean microarray signal, the correlation between the intervals' median of the averages and their proportion of protective expression patterns (the relationship studied in Shih et al 2004) was 0.188 (P = 0.427).…”
Section: Discussionmentioning
confidence: 99%
“…be increased (31,32). HCC SAGE library from single patient may not be as representative as microarray data obtained from hundreds of HCC samples.…”
Section: Discussionmentioning
confidence: 99%
“…If a large number of samples are to be assayed, the phenotype classes should be intermixed in the group assayed at each time. Pooling samples is generally not advantageous [3]. When dual-label arrays are used, there are additional design issues to be addressed concerning whether to use a common reference RNA or to pair the samples from different classes for co-hybridization on each array.…”
Section: Methodsmentioning
confidence: 99%